CHARACTERISTICS OF EFFECTIVE FOOD INTERVENTION PROGRAMS FOR REDUCING BODYWEIGHT ON WORKPLACES - Rizki Apriansyah; Novrikasari; Mohammad Zulkarnain (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Overweight and obesity is a growing problem in the world. As obesity interventions in workplaces on developed countries are immediately rewarded with reduced health insurance cost, workplaces on developing countries are not rewarded with the same benefit. Characteristics of effective food intervention programs are needed to encourage employers for creating low-cost food intervention programs suitable for companies. This literature review aims to reveal characteristics of effective food intervention programs for reducing bodyweight on workplaces. 11 studies using food interventions have been selected from 381 full text articles from ScienceDirect, PubMed and Wiley Online Library for revealing those characteristics using inclusion and exclusion criteria. Six studies which use either specific diet, expert counselling and food substitution are able to give favorable outcomes in the form of reduced bodyweight, better metabolic parameters or reduced calories from food bought on workplace cafeterias. One study in highlight, despite being a pilot study, is effective to reduce bodyweight with only one month of intervention. Specific diet, expert counselling and food substitution are recommended as food intervention. Additionally, such interventions must be tailored to the workplaces, accepted by workers, and doable by employers and researchers. Pilot studies are advisable for finding the perfect formula for future food intervention programs.